Wpływ kształtu i materiału soczewki wewnątrzgałkowej na powstawanie przymglenia torebki tylnej - Szaliński, Marek; Oficjalska-Młyńczak, Jolanta; Zając-Pytrus, Hanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
In this paper we compare 4 groups of intraocular lenses: PMMA, silicone, hydrogel, acrylic and their influence on posterior capsule opacification is discussed. The possible clinical consequences of different shape in optic part of intraocular lens is also described. This article contains also a short presentation of posterior capsule opacification mechanism and intraocular lens materials biocompatibility in in vivo and in vitro experiments.